PERBANDINGAN HASIL BELAJAR FISIKA SISWA YANG MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW DENGAN DISCOVERY-INQUIRY DI SMA - Aristin Raras; Vina Serevina; Anggara Budi Susila (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2015)
This research aims to see how the comparison of of the result of student learning Physics through cooperative learning model of Jigsaw with Discovery-Inquiry. The research has been conducted in February-April 2015 in SMAN 2 Bekasi. The research method which is used is the Quasi-Experiments method The samples were taken two classes from XI SMA Mathmatics and Science. And divided into class experiment 1 and experiment 2. The instrument which is used in the form of a multiple choice test with a score of 0-1 as many as 30 questions and five answers. The results of this study with a statistical test the